KONTINUITAS DAN PERUBAHAN MAKNA LAGU KEBANGSAAN INDONESIA RAYA - Mintargo, Wisnu (Sekolah Pascasarjana UGM, 2012)
The main objective of this paper is to analyze function of âheroicâ Indonesia songs related to the struggle for Indonesian independence ( from 1945 to 1949) from a historical perspective. Through this analysis it is hoped that the process of the past, particularly the history of music development in Indonesia and the background of the use of the âheroicâIndonesia songs, can be reconstructed. Important aspects of Indonesian songs, as this paper shows, include a constructive function for ceremonies and advice for development. The ceremonial character is shown in the song of âIndonesia Rayaâ. the national anthem.